Transformasi Peran Jurnalistik dan Iklim Komunikasi Adaptif: Studi Fenomenologis Wartawan Pos Kupang - Adrianus .; Yustikasari . (JKOMDIS : Jurnal Ilmu Komunikasi Dan Media Sosial, 2026)
Digitalization has caused a shift in the media landscape, which has also presented challenges for local journalism in Indonesia, particularly in peripheral areas like East Nusa Tenggara. Amid declining print media circulation and the increasing dominance of online media, local journalism faces challenges in maintaining its professional identity and social values in the digital public sphere. This study aims to understand how journalists in Harian Pagi Pos Kupang interpret the changes in their professional roles in the era of media convergence, and how these experiences shape new awareness in local journalism practices. This study uses a phenomenological approach (Moustakas, 1994) and involves six active reporters as participants. After data was collected thru in-depth interviews, editorial observations, and digital artifact analysis, it was followed by Braun & Clarke's (2006) thematic analysis to identify significant meanings from the participants' experiences. The research findings revealed five main themes: (1) the transformation of journalists' professional identity from news writers to meaning creators; (2) the negotiation of digital ethics between speed and truth; (3) technological adaptation amidst infrastructure limitations; (4) local-global tensions in maintaining regional journalism identity; and (5) journalists' moral resilience as social responsibility. Overall, local journalism in NTT has not only survived amidst digital disruption but has also created a new media ecology based on moral values, community solidarity, and regional journalistic ethics.